Resistência de genótipos de Vigna unguiculata (L.) Walp.à Aphis craccivora Koch e Crinocerus sanctus Fabricius. - Silva, Jefté Ferreira da (2008)
The cowpea black aphid (Aphis craccivora Koch, 1854) is the most important insect pest of cowpea beans (Vigna unguiculata (L.) Walp.) and is cited as a key pest of this crop. One of the easiest way for its control is by the use of plant resistance to this pest being those natural or induced resistance. The objective of this research was evaluate natural resistance of Vigna unguiculata (L.) Walp. genotypes against black aphid and observe the effect of an resistance inductor, the cis-jasmone on cowpea to control aphid and a true bug and the effects of this material on production parameters. In green house were realized choice and no choice essays to search among 20 genotypes whose would have natural resistance and preference after cis jamone spray at a rate of 50g/ha on the Vita 7 cultivar. It also was realized one bioassay to determine the length of one generation on EPACE 10 and Vita 7 genotypes. The field work was done at Quixada, Ceará State (Brazil) by applying cis-jasmone at the dosage of 39.06 g/ha and 78.13 g/ha using EPACE 10 variety and observe the infestation of Aphis craccivora and bugs and a possible effect on production. The genotypes TVu 408P2, TVu 410, TVu 36 and TVu 1037 presented natural resistance being less susceptible to the aphid. Cis-jasmine had no effect, as resistance is concerned, on aphid population when compared to untreated control plants. O mean generation time of aphid on Vita 7 cultivar was five days and nineteen hours. No insect completed its life cycle on EPACE 10. In field the low insect level, is believed to be due to the natural resistance of genotype used, so no treatment differences were observed. There was also no difference for bug in the evaluation done. Cis-jamone had no effect on production parameters.